Response on Uptake of Nutrients and on Grain Yield from Rice Husk Biochar Application on Oryza sativa L. Grown in a Low Yielding Granary Area of Tanjung Karang, Selangor, Malaysia - Deniel Anak Sang; Rosenani Abu Bakar; Siti Hajar Ahmad; Osumanu Haruna Ahmed; Wan Asrina Wan Yahya; Khairuddin Abdul Rahim (Center for Journal Management and Publication, 2021)
Rice (Oryza sativa L.) production plays a major role in enhancing food security in Malaysia. Lower rice yield and improper soil management practices have raised serious concerns about rice cultivation in Malaysia. The objective of this study was to examine the short-term effects of rice husk biochar (RHB) application on rice yields production on low yielding area for two crop cycles. RHB was applied at the rates of 0, 5, 10, and 20 Mg ha-1. Rice husk biochar was applied one week before rice seeds, of variety MR 263, were directly seeded. Results of the study showed that RHB significantly increased grain yield by 44% and 46% in first and second crop cycles, respectively, as compared to the control treatment. Likewise, RHB amended plots showed significant improvement of rice yield components, viz. productive tiller, panicle length, and weight per panicle, than those of the control plots in the first and second crop cycles. Furthermore, RHB significantly increased nitrogen (N), phosphorus (P) and potassium (K) uptake by 17%, 18%, 29%, respectively, in the first crop cycle, and 26%, 23%, 110%, respectively, in the second crop cycle. RHB application also significantly improved soil available P, exchangeable K and exchangeable Mg in the two crop cycles. Another interesting finding was that the use of RHB reduced soil total carbon loss by 4% to 12% compared with 19% by the control treatment. These findings suggest that RHB can potentially be used as a soil amendment to increase rice yield production, enhance soil nutrient availability and nutrient uptake, as well as reduce carbon losses especially during drought period.